Organic Transistor Arrays Integrated with Finger‐Powered Microfluidics for Multianalyte Saliva Testing. Issue 17 (7th July 2016) - Pappa, Anna‐Maria; Curto, Vincenzo F.; Braendlein, Marcel; Strakosas, Xenofon; Donahue, Mary J.; Fiocchi, Michel; Malliaras, George G.; Owens, Roisin M.
Abstract : A compact multianalyte biosensing platform is reported, composed of an organic electrochemical transistor (OECT) microarray integrated with a pumpless "finger‐powered" microfluidic, for quantitative screening of glucose, lactate, and cholesterol levels. A biofunctionalization method is designed, which provides selectivity towards specific metabolites as well as minimization of any background interference. In addition, a simple method is developed to facilitate multi‐analyte sensing and avoid electrical crosstalk between the different transistors by electrically isolating the individual devices. The resulting biosensing platform, verified using human samples, offers the possibility to be used in easy‐to‐obtain biofluids with low abundance metabolites, such as saliva. Based on our proposed method, other types of enzymatic biosensors can be integrated into the array to achieve multiplexed, noninvasive, personalized point‐of‐care diagnostics. Abstract : A fully integrated multianalyte biosensing platform based on biofunctionalized organic electrochemical transistor microarrays embedded with a "finger‐powered" portable microfluidic is presented. The high sensitivity and selectivity of the system enables noninvasive, label‐free, simultaneous detection of several critical biomarkers such as glucose, lactate, and cholesterol in saliva. This compact, miniaturized healthcare monitoring device paves the way toward next generation point‐of‐care technologies.